2021
DOI: 10.1186/s12909-021-02646-3
|View full text |Cite
|
Sign up to set email alerts
|

Applying visual mapping techniques to promote learning in community-based medical education activities

Abstract: Background Teaching and learning Community-Based Medical Education (CBME) requires the active engagement of students in various activities to cover planned curricular content. CBME being multifaceted involves careful application and formation of links when attending to community health problems and public health issues. Students often depend on factual recall rather than ‘engaging in’, to counteract the broad and comprehensive nature of CBME. This study was conducted to assess the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…There are some gender-based differences in some myopic populations. But studies further concluded that genders did not significantly correlate with myopia, limiting it to some populations [39][40][41][42][43][44]. These significant developments need the consideration of current links between myopia and screen time, particularly in children and in locations where the prevalence of myopia was low before the arrival of digital devices.…”
Section: Discussionmentioning
confidence: 99%
“…There are some gender-based differences in some myopic populations. But studies further concluded that genders did not significantly correlate with myopia, limiting it to some populations [39][40][41][42][43][44]. These significant developments need the consideration of current links between myopia and screen time, particularly in children and in locations where the prevalence of myopia was low before the arrival of digital devices.…”
Section: Discussionmentioning
confidence: 99%
“…So, students can use a mind map to imagine and explore connections between topics, visualize and investigate connections between ideas, grasp the links between concepts, and better understand those concepts as well as the domain to which they belong. Besides, Choudhari et al (2021) explained that a mind map is a learning tool that only provides a visual representation of a topic. In sum, mind maps are viewed as a useful tool for assisting learners in generating their ideas and transforming those ideas into writing through visualization.…”
Section: Using a Mind Map As A Tool To Enhance L2 Writingmentioning
confidence: 99%
“…In contrast, mind maps use a combination of text and graphics to make abstract problems concrete and simplify complex problems by linking fragmented knowledge together, so they are a good supplement to PBL teaching mode. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, mind maps use a combination of text and graphics to make abstract problems concrete and simplify complex problems by linking fragmented knowledge together, so they are a good supplement to PBL teaching mode. [9] We selected 89 standardized clinical residents who rotated in the Department of Emergency Surgery of the First Affiliated Hospital of Anhui Medical University from January 2021 to January 2022 as the study population. We introduced the symptom-based mind maps combined with PBL teaching method into the emergency trauma training teaching in MDT mode and applied the mini-clinical evaluation exercise (Mini-CEX) and direct observation of procedural skills (DOPS) assessments as formative evaluation tools, and achieved satisfactory teaching results, which can provide a basis for promoting the clinical training teaching method of emergency surgery in the future, which is reported as follows.…”
Section: Introductionmentioning
confidence: 99%